TOOLS AND TECHNOLOGIES USED IN ONCOLOGY: ANALYSIS AND SCIENTIFIC APPROACH - Temirova Dilnoza Valiyevna (Western European Studies, 2024)
Oncology is a crucial branch of medicine focused on the detection, treatment, and prevention of cancer. Innovative medical tools and technologies play a key role in early detection and effective treatment of cancer. Tools used in oncology help with diagnosis, treatment, and monitoring. This article provides an overview of some of the key tools used in oncology, their operating principles, and practical applications.
Keywords: detection; provides; treatment; oncology